Spatio-Temporal Patterns In A Semiconductor-Gas-Discharge System: Numerical Solutions And Stability Analysis In 3D Geometry - Rafatov, İsmail (İstanbul Kültür Üniversitesi Yayınları, 2006)
We investigated the spatio-temporal patterns formation in the semiconductor-gas-discharge sys-tem consisting of a short gas-discharge layer sandwiced with a semiconductor layer between planar electrodes to which a de voltage is applied, in three spatial dimensions. We define the model, identify its independent dimensionless parameters, and then present the results of the full time-dependent numerical solutions of the model as well as well of a linear stability analysis of the stationary state. Nuremical solutions and the results of the stability analysis agree well. Numerical results Show that at parameter regime we investigated either purely Hopf bifurcation or Turing-Hopf bifurcation takes place.
Keywords: Pattern Formation; Stability Analysis; Barrier Discharge; Modeling; Numerical Solution; Model Oluşturma; Kararlılık Analizi; Bariyer Deşarj; Modelleme; Sayısal Çözüm